Pengaruh Komposisi Susu Cair terhadap Sifat Reologi dan Potensi Risikonya pada Kecukupan Proses Termal - Ashari Widhiasmoro; Purwiyatno Hariyadi; Eko Hari Purnomo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
The viscosity and density of liquid milk are influenced by temperature and composition. This study aimed to evaluate the effect of differences in liquid milk composition on rheological properties and assess its potential risk to the adequacy of the thermal process. The liquid milk used in this research included fresh milk from three different regions, full-fat recombinant milk (fat content >3%), partially skimmed recombinant milk (fat content >0.5%), and recombinant milk with cocoa solids (fat content >2%). The results showed that in 2022, fresh milk samples from West Java, Central Java, and East Java had total solids of 11.7±0.14%, 11.5±0.14%, and 12.1±0.19%, respectively; fat content of 3.6±0.15%, 4.0±0.13%, and 4.0±0.13%; and protein content of 2.9±0.04%, 2.9±0.06%, and 3.0±0.06%. All samples exhibited Newtonian fluid behavior, with density and viscosity decreasing as temperature increased. Differences in the density and viscosity of liquid milk affected the maximum flow speed in the holding tube but did not significantly impact the F₀ value. In sterilization practices with F₀ values ranging from 5.2 to 10.9 minutes, variations in maximum flow rates among fresh milk from different regions and different types of recombinant milk did not pose a risk to food safety, as the adequacy of the thermal process was still achieved (F₀>3.0 minutes).